N-DIMENSIONS LINEAR THERMOELASTIC SYSTEM IN DOMAINS WITH MOVING BOUNDARY - Quiroga de Caldas, Cruz Sonia (1999)
In this article the authors investigated the existence of solutions for the linear thennoelastic system in a noncylindrical domain ...